Exhibition-discussion technical and scientific training in undergrade students - Gutiérrez-Gonzales, Víctor (2019)
The overall objective was to demonstrate the influence of the exhibition-discussion technique on the scientific training of undergraduate students of the National University of San Cristobal de Huamanga, 2017. The research was carried out on the basis of the collection of data, the references of which were the undergraduate students of the 100 series of the VET of Economics. The research is explanatory, with a quasi-experimental design. The inductive method has been used from population samples with observable subjects, focusing on the results and analysis of fieldwork data, which were subjected to statistical measurement and analysis. Result: the contrast between O1 vs O2 was made. It allows us to observe that the value of W+ -3.428 and the value of the following is the following, so that the alternating hypothesis is assumed and the null hypothesis is rejected, and to be sure that the only difference between the two tests is the program's intervention plan, we can say that, the technique of exposure-discussion significantly influences scientific training in students of Economics.